2015
DOI: 10.1039/c5sm01521a
|View full text |Cite
|
Sign up to set email alerts
|

Correlating antimicrobial activity and model membrane leakage induced by nylon-3 polymers and detergents

Abstract: Most antimicrobial peptides act upon target microorganisms by permeabilizing their membranes. The mode of action is often assessed by vesicle leakage experiments that use model membranes, with the assumption that biological activity arises from permeabilization of the lipid bilayer. The current work aims to extend the interpretation of vesicle leakage results and examine the correlation between vesicle leakage and antimicrobial activity. To this end, we used a lifetime-based leakage assay with calcein-loaded v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 77 publications
2
59
0
Order By: Relevance
“…These results imply that the α/β CPMB kill S. aureus quickly by disrupting bacteria cell membrane using its multiple sidechain poly-α-L-lysine that is generally considered as HDP mimics. Similar observations have been reported for HDP and their mimics because these types of antimicrobial agents target cell membrane to have antibacterial activity [72].…”
Section: µMol Lsupporting
confidence: 80%
“…These results imply that the α/β CPMB kill S. aureus quickly by disrupting bacteria cell membrane using its multiple sidechain poly-α-L-lysine that is generally considered as HDP mimics. Similar observations have been reported for HDP and their mimics because these types of antimicrobial agents target cell membrane to have antibacterial activity [72].…”
Section: µMol Lsupporting
confidence: 80%
“…149 Gellman et al showed that their HDP-mimetic nylon-3 polymer selectively disrupts lipid membranes depending on the lipid composition; the polymer efficiently disrupts liposomes of DOPG/DOPG (mimicking E. coli membranes), but not those of POPC (mimicking mammalian cell membranes). 147 These data suggest that optimized formulations of HDP-mimetic polymers are inherently more active against membranes that possess anionic charge and negative curvature. Fluorescence lifetime assays can distinguish between all-or-none leakage (a fraction of the vesicles released all of their contents) versus graded leakage (all vesicles released a portion of their contents).…”
Section: Liposomes As Model Membranesmentioning
confidence: 92%
“…146 Despite its simplicity, dye leakage provides a useful demonstration of the inherent membrane-disputing ability of a polymer, which may contribute to the mechanism of antibacterial and hemolytic action (at least in part). 147,148 This technique has been employed for polynorbornenes, 56 polymethacrylates, 43 and nylon-3 copolymers. 147 The fundamental basis for cell-type selectivity can be observed by comparing dye leakage from liposomes that mimic anionic bacterial membranes (e.g.…”
Section: Liposomes As Model Membranesmentioning
confidence: 99%
See 2 more Smart Citations